2022
DOI: 10.18502/ijm.v14i4.10239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eliminating hdcA gene of Staphylococcus epidermidis TYH1 on Histamine production

Abstract: Background and Objectives: The possible adverse effect of histamine on human health has made it a detrimental aspect to the quality and safety of many fermented food products especially fish sauce. Materials and Methods: In the present study, hdcA gene in Staphylococcus epidermidis TYH1 was knocked out and its effect on histamine production was evaluated. HdcA encodes histidine decarboxylase, an enzyme that produces histamine from histidine. Both strains of TYH1, the wild type (WT) and mutant (∆hdcA) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The application of basic electrolyte and negative pressure on the separation enhanced the separation of the isobaric amino acids leucine and isoleucine. 30 kV of voltage, and a hydrodynamic injection at 50 mbar for 3 s. This CZE-UV method confirmed the effectivity of the gene elimination due to histamine was not observed in the sample [28]. Different studies have shown that histamine is degraded by staphylococcal strains.…”
Section: Amino Acids Biogenic Amines Heterocyclic Amines and Other Ha...supporting
confidence: 73%
See 4 more Smart Citations
“…The application of basic electrolyte and negative pressure on the separation enhanced the separation of the isobaric amino acids leucine and isoleucine. 30 kV of voltage, and a hydrodynamic injection at 50 mbar for 3 s. This CZE-UV method confirmed the effectivity of the gene elimination due to histamine was not observed in the sample [28]. Different studies have shown that histamine is degraded by staphylococcal strains.…”
Section: Amino Acids Biogenic Amines Heterocyclic Amines and Other Ha...supporting
confidence: 73%
“…An allelic replacement of S. epidermidis was carried out to eliminate de gene and the histamine production was controlled by its determination by CZE–UV. CZE–UV analysis allowed a rapid and selective determination of histamine in 8 min using hydroxyisobutyric acid (60 mM) and sodium hydroxide (10 mM) at pH 3.3 as BGE, 30 kV of voltage, and a hydrodynamic injection at 50 mbar for 3 s. This CZE–UV method confirmed the effectivity of the gene elimination due to histamine was not observed in the sample [28]. Different studies have shown that histamine is degraded by staphylococcal strains.…”
Section: Amino Acids Biogenic Amines Heterocyclic Amines and Other Ha...mentioning
confidence: 79%
See 3 more Smart Citations